Analisis Persepsi Siswa Berdasarkan Gender Terhadap Pembelajaran Biologi di Dalam Kelas - Syarifah Farissi Hamama; Syarifah Fadiya Hallaby; Santi Ramona (Jurnal Dedikasi Pendidikan, 2019)
The aims of this research was to determine the differences between female and male students’ perception toward Biology subject in classroom environment. This research was conducted at SMAN 4 Banda Aceh, with a total sample of 103 students. A Krejcie-Morgan table was used as the sampling technique. Students’ perception was collected by using “What is Happening in this Class (WIHIC)” questioner which has been translated into Indonesian. Collected data was analysed by the Independent T-Test. The results showed that the only differences perception betwen male and female students on actual classroom environtment was on teacher support (0,65). However, male and female students perception on the expected situation in classroom environment were differ on most aspect, except on student involvement (-0,17).